Acute ischemic stroke induces magnetic resonance susceptibility signs dominated by endothelial nitric oxide synthase activation. Issue 4 (31st October 2020) - Chen, Chiao‐Chi V.; Chang, Chen; Lin, Ming‐Fang; Huang, Guo‐Shu; Chan, Wing P.
Abstract : Purpose: Acute ischemic stroke induces deoxyhemoglobin accumulation around the ischemic region while activating endothelial nitric oxide synthase (eNOS) coupling and the subsequent release of nitric oxide (NO). Because deoxyhemoglobin is a natural NO spin trap, its interplay with NO could be prominent during acute stroke. Its interaction with NO has been shown to induce overt paramagnetic signals in vitro; our goal was to investigate whether this interplay can be detected using MRI. Methods: To verify the in vivo image effects using the deoxyhemoglobin‐NO interaction during acute stroke, eNOS states were manipulated in an animal model of acute ischemia, and the susceptibility signals, cerebral perfusion, and infarction were assessed noninvasively via MR susceptibility weighted imaging (SWI). Results: Occlusion of the right middle cerebral artery increased eNOS coupling and susceptibility signals in the ischemic cortex while abolishing regional cerebral blood flow. Pharmacological eNOS blockage led to weakened susceptibility signals in the ischemic cortex as well as worsened tissue survival. Consistently, abolishment of eNOS coupling through genetic editing reduced the regional susceptibility signals in the ischemic cortex, causing large infarcts. Conclusion: Upregulation of eNOS during acute ischemia sustains tissue viability through the interaction between NO and deoxyhemoglobin. This interplay can be traced in vivo using SWI and can be considered a sensitive marker revealing the delicate oxygenation status of the ischemic tissue, therefore, guiding the management of acute stroke in clinical settings.